Reference Values of M-mode Echocardiographic Parameter in Adult Toy Breed Dogs - Isayama, Noriko; Uchimura, Yusuke; Sasaki, Kenta; Maeda, Erika; Takahashi, Toshihisa; Watanabe, Megumi (Frontiers in Veterinary Science, 2022)
Introduction: Myxomatous mitral valve disease (MMVD) is one of the most common heart diseases in dogs, and there is a dearth of reports that have investigated reference values for left ventricular end‐diastolic internal diameter corrected for body weight (LVIDDN) exclusively in toy breeds. Animals: Eighty-six client-owned healthy dogs weighing <5 kg, including Toy Poodles, Chihuahuas, Yorkshire Terriers, Papillon, and other small breeds or small mixed breeds (mixed breed, Pomeranian, dachshund, Shih Tzu, and Maltese). In this retrospective single-center study, data were collected from dogs attending clinic for annual checkup between April 2014 and March 2021. Materials and Methods: Experienced echocardiographers performed transthoracic echocardiography, with reference ranges established using healthy dogs. Measurements of body weight (BW), heart rate, and several echocardiographic variables were obtained. The association between BW and echocardiographic parameters was assessed by linear regression analyses. M-mode measurements were obtained and normalized using equations developed from the regression analyses. Results: The LVIDDN value for 95% of dogs weighing <5 kg was achieved by dividing the M-mode measurement by BW raised to the power 0.332. The upper limit of the prediction interval for breeds weighing <5 kg was much lower than the value currently applied. Conclusions: We propose a reference LVIDDN value of ≥1.6 for the diagnosis of stage B2 MMVD in toy breed dogs. The results of our study will guide clinicians in deciding when to start treatment for MMVD in small breed dogs.